Predation of Diatraea saccharalis eggs and neonates by the earwig Euborellia annulipes - de Souza, Joice Mendonça [UNESP]; Seleghim, Aimée Regali [UNESP]; da Silva Nunes, Gilmar [UNESP]; Truzi, Caio Cesar [UNESP]; Vieira, Natalia Fernanda [UNESP]; De Bortoli, Sergio Antonio [UNESP] (Elsevier, 2022)
Diatraea saccharalis (Lepidoptera: Crambidae) is a key sugarcane pest in South America. The prohibition of crop burning and soil conservation programs have allowed several natural enemies of sugarcane borer to increase population their densities. The earwig Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) is a generalist predator often found in sugarcane fields that will prey on eggs and larvae of D. saccharalis. This study used choice and no-choice tests to assess consumption of D. saccharalis eggs and neonate larvae by different earwig life stages in a 12 h period. The mean predation rates of E. annulipes nymphs and adults were estimated and their relative preference for eggs versus neonate larvae was analyzed by Manly's preference index. The functional responses of fourth and fifth instar nymphs and male and female adults were evaluated over 24 h. The mean predation rate was highest on neonate larvae, and this life stage preferred the most preferred (ß = 0.98). Fourth and fifth instars and adults consumed more prey (both eggs and larvae) than earlier life stages, and their functional responses varied with life stage of both predator and prey. Females exhibited a type III response when preying on neonate larvae, which had the shortest handling time. All life stages of E. annulipes consumed both eggs and larvae, preferring the D. saccharalis neonate larvae.
Keywords: Biocontrol; Functional response; Preference index; Sugarcane